Remnant Repair-enhanced Polyethylene Terepthalate Artificial Ligament Graft Ligamentization - Li, H.; Chen, J.; Chen, S. (International Journal of Sports Medicine, 2015)
The aim of this study was to investigate whether augmented remnant repair could enhance polyethylene terepthalate (PET) artificial ligament graft ligamentization. 12 female goats underwent ACL reconstruction with PET artificial ligament graft in the right knees. Right knees in 6 goats were reconstructed with augmented remnant repair (Remnant group), whereas the other 6 goats had no augmented remnant repair comprised the Control group. 3 goats in each group were randomly sacrificed at 6 months and 12 months respectively after surgery. The intra-articular parts of the reconstructed grafts were harvested for histological evaluation. Well-vascularized tissue ingrowth within the artificial ligament was observed in the remnant group at 12 months postoperatively. Collagen-I content of graft was significantly higher in the Remnant group than in the Control group at each time point (p<0.05). The relative expression of collagen-III positive area of the remnant-preserved group was significantly higher than that of the Control group at 12 months (p=0.005). The vascular endothelial growth factor (VEGF)-positive or CD31-positive area in the graft appeared higher in the Remnant group compared with the Control group at 6 months. Remnant repair enhanced the revascularization and remodeling of the PET artificial ligament in ACL reconstruction.
Keywords: polyethylene terepthalate; augmented remnant repair; ligamentization; artificial ligament; ACL